Lopinavir-ritonavir versus hydroxychloroquine for viral clearance and clinical improvement in patients with mild to moderate coronavirus disease 2019 - JW Kim; Eun Jin Kim; Hyun Hee Kwon; Chi Young Jung; Kyung Chan Kim; Jung‐Yoon Choe; Hyo‐Lim Hong (2020)
Background/Aims The efficacies of lopinavir-ritonavir or hydroxychloroquine remain to be determined in patients with coronavirus disease 2019 (COVID-19). To compare the virological and clinical responses to lopinavir-ritonavir and hydroxychloroquine treatment in COVID-19 patients. Methods This retrospective cohort study included patients with COVID-19 treated with lopinavir-ritonavir or hydroxychloroquine at a single center in Korea from February 17 to March 31, 2020. Patients treated with lopinavir-ritonavir and hydroxychloroquine concurrently and those treated with lopinavir-ritonavir or hydroxychloroquine for less than 7 days were excluded. Time to negative conversion of viral RNA, time to clinical improvement, and safety outcomes were assessed after 6 weeks of follow-up. Results Of 65 patients (mean age, 64.3 years; 25 men [38.5%]), 31 were treated with lopinavir-ritonavir and 34 were treated with hydroxychloroquine. The median duration of symptoms before treatment was 7 days and 26 patients (40%) required oxygen support at baseline. Patients treated with lopinavir-ritonavir had a significantly shorter time to negative conversion of viral RNA than those treated with hydroxychloroquine (median, 21 days vs. 28 days). Treatment with lopinavir-ritonavir (adjusted hazard ratio [aHR], 2.28; 95% confidence interval [CI], 1.24 to 4.21) and younger age (aHR, 2.64; 95% CI 1.43 to 4.87) was associated with negative conversion of viral RNA. There was no significant difference in time to clinical improvement between lopinavir-ritonavir- and hydroxychloroquine-treated patients (median, 18 days vs. 21 days). Lymphopenia and hyperbilirubinemia were more frequent in lopinavir-ritonavir-treated patients compared with hydroxychloroquine-treated patients. Conclusions Lopinavir-ritonavir was associated with more rapid viral clearance than hydroxychloroquine in mild to moderate COVID-19, despite comparable clinical responses. These findings should be confirmed in randomized, controlled trials.